Impact of academic based information technological systems toward the improvement of social productivity among higher studies program followers; a study based on microsoft office 365 system - Suraj, M.R.; Perera, R.A.S.A. (University of Jaffna, 2019)
People in high modern competitive world use many technological systems, packages to improve the productivity of their daily works. In the academic sector in Sri Lanka uses many academic-related IT Systems are used to obtain optimal benefits from it. This research article is focused on finding the impact of very useful and widely used It system called Microsoft Office 365 towards the improvement in social productivity. The main object of the study is to identify the impact of Microsoft Office 365 system dimension towards the social productivity development of the higher education followers. Sub research objectives are, (1) to identify the most effective impact of Microsoft Office 365 system dimension towards the social productivity development of higher education followers. (2) to identify whether there a significant difference between in impact of Microsoft Office 365 system on social productivity development between genders. Primary data are collected from 65 sample units which are drawn from the National Institute of Business management Galle centre for this study. The stratified sampling method is used and Regression and correlation analysis and correlation analysis comparison methods and tools are used to analyze the data. Analyzed data revealed that Microsoft Office 365 system makes a significant contribution towards the improvement of Social productivity of higher studies followers in National Institute of Business Management Galle Centre. The highest impact factor is the file sharing option in MS office 365 system. Least impact factor of Office 365 system is collaborative Environment facility of the software and it negatively impacts towards the improvement of social productivity. Male higher studies followers use more options in the Microsoft office 365 than the female higher studies followers. Both are preferred file sharing option in the Microsoft office 365 than other options which impact to improvement in social productivity. Among male users file sharing option is well known and least preferred one is Collaborative Environment Facility. Among female users’ highest impact option is file sharing option that they can share lecture notes and other academic materials. But the least preferred option is the facility of storage management towards the enhancement in social productivity.
Keywords: Social productivity; Microsoft office 365; Academic IT systems